2011
DOI: 10.3103/s1068373911020026
|View full text |Cite
|
Sign up to set email alerts
|

The tropopause slope as a characteristic of its deformation

Abstract: The slope of the tropopause is calculated from the data of its height in the points of a regular grid. From the NCEP Reanalysis-2 for 1990-2007, the slope angles are calculated of the tropopause approximated by different constant values of Ertel potential vorticity within the latitude band of 30°-70°N. Effects of horizontal resolution of the data under use on the calculation results are studied on the basis of ten-day samples of objective analysis by UKMO, NCEP, and operative objective analysis of Hydrometeoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The presentation of dy namic tropo pause in the form of a ma te rial sur face en ables ob serv ing the STE fea tures in the zones of its de for ma tion [1]. The ar eas of the tropo pause highs are of ten called "domes," and those of the tropo pause lows are called "folds.…”
Section: Quan Ti Ta Tive Es Ti Mates Of Strato Sphere-tro Po Sphere Ementioning
confidence: 99%
“…The presentation of dy namic tropo pause in the form of a ma te rial sur face en ables ob serv ing the STE fea tures in the zones of its de for ma tion [1]. The ar eas of the tropo pause highs are of ten called "domes," and those of the tropo pause lows are called "folds.…”
Section: Quan Ti Ta Tive Es Ti Mates Of Strato Sphere-tro Po Sphere Ementioning
confidence: 99%
“…The main characteristic is the tropopause height H tr ; also, the tropopause slope values with respect to the Earth's surface were calculated as a measure of deformation of the troposphere-stratosphere interface. The technique of the tropopause slope calculation is described in detail in [1].…”
Section: Introductionmentioning
confidence: 99%
“…Such situations were analyzed on the basis of observational data obtained in 2009 [Ivanova, 2011] and 2009-2011 [Ivanova, 2013]. It was shown that a rapid increase (decrease) in the TOC is unambiguously associated with a descent (ascent) of the tropopause position.…”
Section: Total Contentmentioning
confidence: 99%
“…A method of calculation of the tropopause slope on basis of data about its height presented on regular grid is proposed in (Ivanova, 2011). Based on NCEP2 reanalysis data over 1990-2007, the tilt angles of the tropopause are calculated by approximating it by different isoscalar surfaces of Ertel's potential vorticity in the latitude band 30-70°N.…”
Section: Large-scale Processes and The Weather Forecastmentioning
confidence: 99%